2023
DOI: 10.3390/ani13142294
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Co-Occurrence Pattern Analysis of Cecal and Jejunal Microbiota in Two Rabbit Breeds

Abstract: This study aimed to evaluate the productive performance and microbiota variation in the jejunum and cecum of two rabbit breeds with different growth rates. This study was carried out on Native Middle-Egypt Breed (NMER) and Giant Flanders (GF) rabbits from 5 weeks to 12 weeks of age. Twenty NMER (NM) and GF male rabbits were slaughtered, and the jejunum and cecum tracts were collected to assay gut microbiota composition via 16S ribosomal RNA (rRNA) gene sequencing and histology examination. At 12 weeks of age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…As an important part of the large intestine, the cecum tissues play an important role in the digestion and reabsorption of food nutrition. Studies have shown that the cecum of rabbits is well-developed and can be used as a good intestinal model to study the pathogenesis of animal digestive diseases ( Dabbou et al., 2019 ; Abdel-Kafy et al., 2023 ). Therefore, this study aimed to find the interaction mechanisms among host genes and gut microbiota in the cecum tissues of rabbits fed with a high-fat diet in order to provide a basis for improving and intervening in animal and human intestinal metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…As an important part of the large intestine, the cecum tissues play an important role in the digestion and reabsorption of food nutrition. Studies have shown that the cecum of rabbits is well-developed and can be used as a good intestinal model to study the pathogenesis of animal digestive diseases ( Dabbou et al., 2019 ; Abdel-Kafy et al., 2023 ). Therefore, this study aimed to find the interaction mechanisms among host genes and gut microbiota in the cecum tissues of rabbits fed with a high-fat diet in order to provide a basis for improving and intervening in animal and human intestinal metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…As an important part of the large intestine, the cecum tissues play an important role in the digestion and reabsorption of food nutrition. Studies have shown that the cecum of rabbits is welldeveloped and can be used as a good intestinal model to study the pathogenesis of animal digestive diseases (Dabbou et al, 2019;Abdel-Kafy et al, 2023). Therefore, this study aimed to find the interaction mechanisms among host genes and gut microbiota in the cecum tissues of rabbits fed with a high-fat diet in order to provide a basis for improving and intervening in animal and human intestinal metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%